Micro encapsulation of Naproxen By Complex Coacervation and Aqueous Colloid Dispersion Part ( 1 ) - N.Abood, Ahmad; I. Khalil, Yehia (Iraqi Journal of Pharmaceutical Sciences, 2017)
Naproxen is a non steroidal anti inflammatory and antipyretic drug which has local irritation effect on the stomach, and unpleasant taste, besides bad flowability and light sensitivity .The drug was prepared as microcapsules by complex coacervation method using acacia-gelatin coating materials , and aqueous colloid polymer dispersion method ( ACPD ), using ethyl cellulose and sodium alginate coating materials . The results indicated that microcapsules prepared by 2:1 core:wall ratio is the best for both methods, with an average encapsulation efficiency (75%) and avarege yield (90%) . Moreover the drug release was affected mainly by core : ratio ,pH enviroment and method of microencapsulation . Key words: Naproxen,Microcapsule , Aqueaus colloid polymer dispersion